2006
DOI: 10.1300/j064v28n01_09
|View full text |Cite
|
Sign up to set email alerts
|

On-Farm Productivity of Relay-Cropped Mucuna and Lablab in Smallholder Crop-Livestock Systems in Northwestern Kenya

Abstract: Declining soil fertility and limited quantity and quality of livestock feeds are major constraints to agricultural production in northwestern Kenya. Legumes used as green manures may aid in overcoming soil nutrient depletion and lack of fodder. Relay-cropped mucuna (Mucuna pruriens (L.) DC. var. Utilis (Wright) Bruck) and lablab (Lablab purpureus (L.) Sweet cv. Rongai) were evaluated as alternatives to E. M. Nyambati and S. C. Rono are affiliated with Kenya Journal of Sustainable Agriculture 2006.28:97-116.dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Almost all of these African initiatives have included and continue to include one popular late-maturing forage cultivar, cv. Rongai (Makembe and Ndlovu 1996; Fischler and Wortmann 1999; Haque and Lupwayi 2000; Wortmann et al 2000; Shehu et al 2001; Mureithi et al 2003; Amodu et al 2004; Nworgu and Ajayi 2005; Nyambati et al 2006; Abeke et al 2007; Ojiem et al 2007; Abeke et al 2008; Mubiru and Coyne 2009) and, as a result, the potential role of the species as a pulse or vegetable in Africa is likely to be severely underestimated. Only recent work at ILRI in Ethiopia and CSIRO in Australia (Pengelly and Maass 2001) and, subsequently, in southern Africa (Whitbread and Pengelly 2004) explored a much larger range of accessions for feed and food and identified germplasm, which was well adapted to drier climates and crop use.…”
Section: Four Thesesmentioning
confidence: 99%
“…Almost all of these African initiatives have included and continue to include one popular late-maturing forage cultivar, cv. Rongai (Makembe and Ndlovu 1996; Fischler and Wortmann 1999; Haque and Lupwayi 2000; Wortmann et al 2000; Shehu et al 2001; Mureithi et al 2003; Amodu et al 2004; Nworgu and Ajayi 2005; Nyambati et al 2006; Abeke et al 2007; Ojiem et al 2007; Abeke et al 2008; Mubiru and Coyne 2009) and, as a result, the potential role of the species as a pulse or vegetable in Africa is likely to be severely underestimated. Only recent work at ILRI in Ethiopia and CSIRO in Australia (Pengelly and Maass 2001) and, subsequently, in southern Africa (Whitbread and Pengelly 2004) explored a much larger range of accessions for feed and food and identified germplasm, which was well adapted to drier climates and crop use.…”
Section: Four Thesesmentioning
confidence: 99%
“…Moreover, it has been shown that both under tilling and no-till cultivation conditions, the use of cover crops captures the excess mineral N remaining in the soil during winter and early spring periods, thus limiting the amount of mineral N that can leach into ground water [ 40 – 42 ]. Furthermore, several studies have demonstrated that due to their ability to fix atmospheric N, legume cover crops have a beneficial impact on crop production [ 43 46 ] by increasing soil fertility, notably by increasing the N content [ 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of the need for commercial feed/supplements/concentrates through higher feed efficiency and quality: Snijders et al, 2011;Lukuyu et al, 2013; B. Reduction of the need for off-farm manure or chemical fertilizers: Nyambati et al, 2006;Douxchamps et al, 2010Douxchamps et al, , 2014 Baptistella et al, 2020;Olaya-Montes et al, 2020;Vazquez et…”
Section: Input Reductionmentioning
confidence: 99%